The knowledge of children and adolescents with sickle cell anemia about their self-care (Research, Society and Development, 2022)
Objective: To identify the knowledge that children and adolescents with Sickle Cell Anemia (SCA) have in relation to self-care, analyze the knowledge regarding the self-care of children and adolescents with SCA and discuss the importance of health professionals in the self-care practice of this public. Methodology: Descriptive study with a qualitative approach, carried out at the oncohematology outpatient clinic of a public pediatric hospital in the Federal District, with participants from 6 to 17 years old, based on the dynamics of creativity and sensitivity Corpo Saber. The analysis of the data obtained was thematic. Results: The study had 20 participants in total. From the interviews, three thematic units were detected. Discussion: Self-care is required of any individual as they become capable, but for people diagnosed with SCA, the requirements become greater, considering that the risk of disease complications increases if proper care is not provided. Conclusion: Since childhood, individuals with SCA must be effectively guided to live with their condition, reducing the related risks. Health professionals must be attentive and prepared to understand the gaps in their patients knowledge, and interfere with correct counseling, generating greater adherence to self-care.